PENGEMBANGAN BISNIS PENJUALAN SPAREPART KENDARAAN DENGAN MEDIA SISTEM INFORMASI - Ahmad Alvin Adriansyah; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2023)
As we know, we have seen many types of businesses running around us, one of which is the sale of motor vehicle spare parts. Spare parts are goods that consist of several types of components and have certain functions. There are many shops, both official and private, that sell spare parts, but there are still some shops that use conventional information systems in their sales process, where conventional sales have weaknesses such as not being well known about the business and the potential for errors in the process or data calculations. So many errors occur in calculating stock of goods, finances, sales receipts. With this problem, in selling spare parts you have to make an innovation, namely the author will describe several innovations in information system media that can be used in conducting sales business. It is hoped that it will be able to help management in making decisions and also running business operations, increasing efficiency, productivity and increasing spare parts sales.